Stagnasi dan Taqlid dalam Sejarah Tasyri’: Analisis Epistemologis atas Kemunduran Ijtihad pada Abad 4–19 H - Muhammad Ashif Arifin; Nike Putri Ramadhani; Nurhidayah Lailaturrizky; Umar Al-Faruq (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
Tarikh Tasyri’ is a vital concept in Islamic studies, referring to the period of the implementation of Sharia law. This article explores the significance, historical context, philosophical underpinnings, and relevance of Tarikh Tasyri’. The study examines its evolution from the early days of Islam to contemporary times, highlighting its role in shaping Islamic legal frameworks and social structures. The article emphasizes the importance of understanding Tarikh Tasyri’ in addressing modern challenges and upholding Islamic values in a globalized world. Through library research, data from books, journals, and articles are analyzed. The findings demonstrate that Tarikh Tasyri’ is crucial for understanding Islamic law's development and its social impact. The study also reveals that stagnation during the periods of jumud and taqlid not only hindered legal practice but also restricted the development of adaptive ijtihad methodologies. This stagnation obstructed Islamic legal reform well into the modern era. Therefore, a deep understanding of the epistemological effects of jumud is essential for revitalizing contemporary Islamic law and ensuring its relevance in the face of globalization